Marketing a country: promotion as a strategic marketing tool for attracting foreign direct investment-evidence from ghana investment promotion center (gipc) - JAGRE KINGSFORD KWAKU (KNUST, 2024)
A thesis submitted to the institute of distance learning, Kwame Nkrumah university of science and technology, kumasi in partial fulfilment for the degree of master of science marketing